Caloric Restriction May Help Delay the Onset of Frailty and Support Frailty Management - Liu, Pan; Li, Yun; Ma, Lina (Frontiers in Nutrition, 2021)
Frailty is an age-related clinical syndrome that may increase the risk of falls, disability, hospitalization, and death in older adults. Delaying the progression of frailty may help improve the quality of life in older adults. Caloric restriction (CR) may extend lifespan and reduce the risk of age-related diseases. However, few studies have explored the relationship between CR and frailty. In this review, we focused on the impact of CR on frailty and aimed to identify potential associated mechanisms. Although CR may help prevent frailty, further studies are required to determine the underlying mechanisms and specific CR regimens suitable for use in humans.